АҲОЛИГА ХИЗМАТ КЎРСАТИШ СОҲАЛАРИНИ ТАДҚИҚ ЭТИШНИНГ ИЛМИЙ - УСЛУБИЙ АСОСЛАРИ - Узақбаев, Қ.К. (SCIENCE and SOCIETY, 2022)
In the global economy, the service sector networks or the third sector is the most advanced. In this article, from a geographical perspective, service sector networks are evaluated.